2018
DOI: 10.1080/2162402x.2018.1542245
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating T cells and PD-L1 expression in childhood malignant extracranial germ-cell tumors

Abstract: Although pediatric malignant extracranial germ-cell tumors (meGCTs) are among the most chemosensitive solid tumors, a group of patients relapse and die of disease. To identify new markers predicting clinical outcome, we examined the prognostic relevance of tumor-infiltrating T lymphocytes (TILs) and the expression of PD-1 and PD-L1 in a cohort of pediatric meGCTs by in situ immunohistochemistry. MeGCTs were variously infiltrated by T cell-subtypes according to the tumor subtype, tumor location and age at diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 48 publications
4
15
0
1
Order By: Relevance
“…In pediatric patients with extracranial GCTs, high CD3+ T-cell infiltration, both in tumor nests and septa, indicated a favorable outcome [ 50 ]. Interestingly, PD-L1-positive TILs were reported only in single cases (one yolk sac tumor and three embryonal carcinomas).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pediatric patients with extracranial GCTs, high CD3+ T-cell infiltration, both in tumor nests and septa, indicated a favorable outcome [ 50 ]. Interestingly, PD-L1-positive TILs were reported only in single cases (one yolk sac tumor and three embryonal carcinomas).…”
Section: Discussionmentioning
confidence: 99%
“…), precludes any clear conclusions. The summary of the studies investigating the expression of PD-L1 in GCTs is presented in Table 6 [ 17 , 18 , 19 , 21 , 44 , 45 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of PD-1 and PD-L1, along with the prognostic relevance of TIL, was also investigated in pediatric gonadal germ cell tumors, a heterogeneous group of tumors which represent 3–5% of all childhood cancers occurring before 15 years of age, and 15% of neoplasms in adolescents aged 15–19 years [ 111 ]. Three different cancer phenotypes were identified that were tumors (i) with no T cell infiltration, (ii) highly infiltrated by PD-1 + CD8 + T cells and (iii) highly infiltrated by CD8 + T cells within an immunosuppressive TME characterized by Treg cells and PD-L1 + neoplastic cells.…”
Section: Ic As Immunotherapeutic Targets In Pediatric Solid Cancersmentioning
confidence: 99%
“…Alpha-fetoprotein (AFP) serves as posttherapeutic follow-up parameter 56 203 . The influence of immune checkpoint inhibitors on immature teratomas that are considered as “cold, deserted tumors” abandoned by the immune system 24 is currently unknown.…”
Section: Cervical Soft Tissuesmentioning
confidence: 99%
“…Bösartige unreife Tumore werden zusĂ€tzlich chemotherapeutisch behandelt, Alpha-Fetoprotein (AFP) dient als posttherapeutischer Verlaufsparameter 56 203 . Der Einfluss von Immuncheckpoint-Inhibitoren auf unreife Teratome, welche als „kalte, vom Immunsystem verlassene“ Tumore gelten 24 , ist bislang nicht geklĂ€rt.…”
Section: 32 Teratomeunclassified